2010
DOI: 10.1590/s0004-27302010000200007
|View full text |Cite
|
Sign up to set email alerts
|

Osteoporosis and inflammation

Abstract: SUMMARYSeveral inflammatory diseases such as rheumatoid arthritis, systemic lupus erythematosus, inflammatory bowel disease, celiac disease, cystic fibrosis and chronic obstructive pulmonary disease have been associated to bone resorption. The link between osteoclast, macrophage colony stimulating factor and pro-inflammatory cytokines, especially tumor necrosis factor-α and interleukin-1 explain the association between inflammation and osteoporosis. These diseases are related to osteoporosis and high fracture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
138
0
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 198 publications
(151 citation statements)
references
References 51 publications
2
138
0
7
Order By: Relevance
“…Secondarily, it may be due to prolonged corticosteroid therapy, nutritional changes such as poor calcium intake, vitamin D deficiency, alcoholism, and smoking. [9][10][11][12] In our study, we observed that, in women with IBD, fracture cases were more frequent among smokers, a factor already pointed out in another study, 9 which associated smoking with reduction of BMD and with increased risk of fractures. Souza et al described that the number of patients with low BMD between the two groups of IBD is equivalent.…”
Section: Discussionmentioning
confidence: 56%
“…Secondarily, it may be due to prolonged corticosteroid therapy, nutritional changes such as poor calcium intake, vitamin D deficiency, alcoholism, and smoking. [9][10][11][12] In our study, we observed that, in women with IBD, fracture cases were more frequent among smokers, a factor already pointed out in another study, 9 which associated smoking with reduction of BMD and with increased risk of fractures. Souza et al described that the number of patients with low BMD between the two groups of IBD is equivalent.…”
Section: Discussionmentioning
confidence: 56%
“…No physical activity was found in about 40% of the patients, independently of the rheumatic disease, and the prevalence of falls was high, in particular in RA and PMR (about 20%). Immobilization due to pain from inflamed joints and impairment of physical activity are known key factors related to low BMD and are common in patients suffering from rheumatic diseases (55). The risk of falls may be higher in RA patients because of lower limb joint disease and muscle weakness (due to GCs therapy and disuse) (56).…”
Section: N Discussion and Conclusionmentioning
confidence: 99%
“…RANK-RANKL osteoprotegerin system, modulated by vitamin D, directly influences the release of pro inflammatory cytokines. It is now known that vitamin D deficiency makes muscles weaker and that vitamin D repletion boosts muscle strength [17].…”
Section: Discussionmentioning
confidence: 99%